A study on the level of knowledge and understanding among muslims towards the concepts, arabic and shariah terms in Islamic insurance (Takaful). - Othman, Mohd Sukki; Abdul Hamid, Mohamad (Eurojournals, 2009)
The word takaful is derived from an Arabic word of kafala which means to guarantee, looking after or trust. The noun takaful is derived from adverbs takafala which literally translates to “looking after one another”. The market share of takaful in insurance industry was only 5.9 percent. It is extremely low compared with conventional insurance despite the existence of takaful in Malaysia for more than 20 years since 1984?. This study tries to investigate this issue by conducting a preliminary study on the level of knowledge and understanding of people among Muslims in Malaysia towards the concepts. Arabic and shariah terms in takaful. A sample of 500 questionnaires distributed , 232 (46.4%) were returned. Surprisingly, majority of the rspondents (67.24%) do not know and understand about ‘tabarru’ which is the main and core feature of takaful that is totally different from conventional insurance. Most of the respondents do not know and understand about the concept that is newly practiced in takaful i.e. al-ujrah (commission) and al-wakalah (agent). Unfortunately, majority of the respondents )68%) do not know and understand about the elements of gharar and maysir which make the conventional insurance is against the principles of shariah. Interestingly, majority of the respondents (74.14%) have agreed with the use of Arabic terms in takaful. It is found that the most reasons quoted by the respondents are to differentiate the takaful from conventional insurance and to show that takaful promotes the Islamic finance products. Some of the findings in this paper may be useful for the companies in heir effort to enhance their marketing and promotion activities.